Efektivitas Implementasi Kebijakan Pendaftaran Tanah Sistematis Lengkap Di Kabupaten Semarang - Ahmad Nursalim; Retno Sunu Astuti; Kismartini Kismartini; Teuku Afrizal (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2021)
Land is an important and inherent element in human life because most of life depends on the soil. The need for land registration is very important in order to secure land rights owned by someone as well as to realize the orderly administration of land in Indonesia. Efforts to accelerate the implementation of land certification have been carried out since the issuance of the LoGA in 1960 through various programs, but until 2016 only 40.07% registered land. These conditions encourage the government to create a Systematic Complete Land Registration (PTSL) policy to accelerate land registration in Indonesia, especially in Semarang Regency. The research method used is a mixture (mixed methods) to answer the research objectives, namely knowing the effectiveness of policy implementation. The theory of policy implementation used in this study tries to explore the driving and inhibiting factors of PTSL policy implementation in Semarang Regency. The results showed that the implementation of the PTSL policy in Semarang District was quite effective but there were still obstacles, namely the socio-economic conditions of the community, limited implementation of human resources, and no pre-certification budget allocation. Recommendations as a step for the government to do are continuing counseling to increase public awareness about the importance of land certificates, realignment and equitable implementation of the workload of implementers, and the allocation of pre-certification budget for weak economy communities.